Effect of operating parameters on denitrification in an anoxic rotating biological contactor - Cortez, Susana (2009)
The presence of nitrate in water and wastewater is a serious environmental problem. Anoxic rotating biological contactors (RBC) are a promising novel technology for nitrate removal. In this study the effect of two carbon/nitrogen (C/N) molar ratios (1.5 and 3.0) on denitrification, using acetate as a carbon source, were investigated in an anoxic bench-scale RBC, treating synthetic wastewater. The effect of different hydraulic retention times (HRTs) and different nitrogen and carbon influent concentrations on the reactor performance, at constant C/N, were also analysed. The average removal efficiency in terms of nitrogen-nitrate was about 90.4% at C/N = 1.5, lowering to 73.7% at C/ N = 3.0. Considering carbon-acetate removal, overall efficiencies of 82.0% and 63.6% were attained at C/N ratios of 1.5 and 3.0, respectively. The increase in nitrogen-nitrate (from 50 to 100 mg N-NO3−L−1) and carbon-acetate influent concentrations and the decrease in HRT, keeping C/N constant, had a slight negative effect in terms of substrate removal. It was found that, for the tested conditions, the use of C/N = 1.5 is advantageous to denitrification. The anoxic RBC was significantly effective at reducing nitrate concentrations within a relatively short HRT. These reactors may be a feasible option for the treatment of nitrate-rich wastewaters.